UNIMED Court Tennis Community Forehand Drive Capability Review - Sihombing, Gulasa Octo Gilbert; Dewi, Rahma; Nurkadri, Nurkadri (Journal Coaching Education Sports, 2022)
The purpose of this study was to determine the level of forehand driveability of the UNIMED tennis community. This research is descriptive. The population in the study was 15 Unimed field tennis community athletes with total sampling, which means that the entire population is the sample in this study. The instrument in this study used the Hewitt tennis achievement test forehand drive to measure forehand driveability. Based on the tests carried out, the forehand drive capability was obtained with an average value of 15.46. The average results obtained from each athlete illustrate that the ability of the UNIMED tennis community's forehand drive is in the sufficient category. One of the factors causing low forehand driveability is the athlete's error in doing footwork. These results indicate that regular and continuous training is necessary to improve forehand driveability, one of which is footwork training.